Translation and Adaptation of the Adult Developmental Coordination Disorder/Dyspraxia Checklist (ADC) into Asian Uzbekistan - Orifjon Saidmamatov; Jasurbek Jammatov; Cláudia Sousa; Rita Barros; Olga Vasconcelos; Paula Rodrigues (MDPI AG, 2023)
Developmental Coordination Disorder (DCD) is a neurodevelopmental condition that emerges in childhood and its symptoms continue through adulthood. The Adult Developmental Coordination Disorders/Dyspraxia Checklist was the first instrument used to screen adults with possible DCD. The psychometric characteristics of the Uzbek version of the scale were explored. An independent translation of the questionnaire from the original version into the Uzbek language was made. The sample comprised 301 Uzbekistan adults, aged between 17 and 42 years old (M = 20.66; SD = 2.26). Analyses were performed using R software (4.1.0). Descriptive analysis, exploratory factor analysis, and evidence of reliability in terms of internal consistency were assessed using the psych package (2.1.6), intraclass correlation coefficients were assessed using the irr package (0.84.1), and weighted Kappa were assessed using vcd package (1.4-10). To analyse the factor structure of the ADC scale, when applied to an Uzbekistan sample, exploratory factor analysis (EFA) was performed. In the Uzbek version, a one-factor structure was identified, and moderated psychometric properties were found, which makes it a possible alternative to the original scale when applied to adults. This Uzbek version reduces respondents' fatigue since it is smaller than the original one. More studies are needed to confirm the cut-off scores of this new version.